Aktywność sportowa i kibicowanie w prozie Krzysztofa Vargi - Tomasz Sahaj (Literatura i Kultura Popularna)
This article presents the work of Krzysztof Varga, a Polish columnist and prose writer of Hungarian descent with particular regard paid those threads that directly relate to various forms of physical activity, sports and fan support. Varga’s sporting interests are most evident in his latest works, especially those of an autobiographical nature. The presence of fan support and sports in general is most notable in his Dziennik hipopotama [Diary of a Hippopotamus], in which the author narrates in the first person. Varga’s original work fits into the narrative created by other sports-fan-oriented Polish writers, whose autobiographical works are animated by various literary and cultural-social discourses.